(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Importance of vegetable oils in food industry is fast growing due to rising popularity of the wholesome food. Application of vegetable oils in different technical branches is connected with tendency to promote utilization of renewable raw materials and production of environmentally friendly products. Vegetable oils can be used for frying and salads as well as spices extracts, food additives, for massages, aromtherapy a.o. Wide field for utilization of vegetable oils is production of biodiesel fuel (fatty acid methyl- and ethylesters). Investigations about stabilization of pumpkin seed and oilseed pumpkin oils with BHT, ascorbylpalmitate and ascorbic acid were carried out. Investigations on oxidative stabilization of rape oil methyl- and ethylesters RME, REE (biodiesel fuels) with antioxidants at room and 60 oC temperature were carried out. Investigations about antioxidant properties of rosemary, basil and ginger extracts were carried out.